2009
DOI: 10.1111/j.1468-3083.2008.02867.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent impetigo herpetiformis successfully treated with methotrexate

Abstract: due to MTX is reported in a small numbers of patients with psoriasis. 5-7 Cutaneous ulceration by MTX toxicity is an exclusion diagnosis, and its pathogenic mechanism may be multifactorial, including direct toxicity of the drug in addition to local factors. 8 Lawrence and Dahl 5 described two type of skin ulceration in patients with psoriasis being treated with MTX. In type 1 ulceration, psoriatic lesions became painful and eroded shortly after starting MTX. Type 2 ulcers occurred in skin clinically uninvolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…Although its absolute safety is difficult to prove, Puig et al [13] reviewed pregnancy outcomes of 219 cases who had been exposed to tumor necrosis factor antagonists and concluded that women who conceived while taking infliximab or other anti-tumor-necrosis-factor-α agents can be reassured regarding the continuation of pregnancy. Other studies have reported the successful treatment of persistent IH lesions using methotrexate or retinoid photochemotherapy [14,15]. However, the critical days for isotretinoin-induced defects appear to be any time between 15 and 40 days after conception, with most studies indicating that of the pregnancies that reach 20 weeks gestation, 25–30% will show malformation [16].…”
Section: Discussionmentioning
confidence: 99%
“…Although its absolute safety is difficult to prove, Puig et al [13] reviewed pregnancy outcomes of 219 cases who had been exposed to tumor necrosis factor antagonists and concluded that women who conceived while taking infliximab or other anti-tumor-necrosis-factor-α agents can be reassured regarding the continuation of pregnancy. Other studies have reported the successful treatment of persistent IH lesions using methotrexate or retinoid photochemotherapy [14,15]. However, the critical days for isotretinoin-induced defects appear to be any time between 15 and 40 days after conception, with most studies indicating that of the pregnancies that reach 20 weeks gestation, 25–30% will show malformation [16].…”
Section: Discussionmentioning
confidence: 99%
“…In some severe cases, it is necessary to increase the dose to 40-60 mg a day to control the symptoms [2,22]. However, some cases reported that the patients were unresponsive to corticosteroid therapy [10,17,22]. In progressive cases, oral cyclosporine is the second-line therapy for IH and antibiotics should be administered to treat or prevent secondary infection [2,9,17,22].…”
Section: Discussionmentioning
confidence: 99%
“…IH mainly afflicts pregnant women during the third trimester of pregnancy but it may also occur in the first trimester of pregnancy, puerperium or menstrual period, and it may even occur in men [8,11,12,13,14]. In patients who suffered from IH before, the disease recurs at an earlier gestational age during a subsequent pregnancy [7,9,10]. Although genetic background is not considered in our literature review, several familial cases have been reported [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations